In vitro activity of sulopenem against 1880 bacterial pathogens isolated from Canadian patients with urinary tract infections (CANWARD, 2014–21). (30th September 2022) - Walkty, Andrew J; Karlowsky, James A; Baxter, Melanie R; Lagace-Wiens, Philippe R S; Adam, Heather J; Zhanel, George G
Abstract: Introduction: There are limited oral antimicrobial options for the treatment of urinary infections caused by ESBL-producing and MDR Enterobacterales. Sulopenem is an investigational thiopenem antimicrobial that is being developed as both an oral and IV formulation. The purpose of this study was to evaluate the in vitro activity of sulopenem versus bacterial pathogens recovered from the urine of patients admitted to or assessed at hospitals across Canada (CANWARD). Materials and methods: The in vitro activity of sulopenem and clinically relevant comparators was determined for 1880 Gram-negative and Gram-positive urinary isolates obtained as part of the CANWARD study (2014 to 2021) using the CLSI broth microdilution method. Results: Sulopenem demonstrated excellent in vitro activity versus members of the Enterobacterales, with MIC90 values ranging from 0.06 to 0.5 mg/L for all species tested. Over 90% of ESBL-producing, AmpC-producing and MDR (not susceptible to ≥1 antimicrobial from ≥3 classes) Escherichia coli were inhibited by ≤0.25 mg/L of sulopenem. Sulopenem had an identical MIC90 to meropenem for ESBL-producing and MDR E. coli . The MIC90 of sulopenem and meropenem versus MSSA was 0.25 mg/L. Sulopenem was not active in vitro versus Pseudomonas aeruginosa (similar to ertapenem), and it demonstrated poor activity versus Enterococcus faecalis (similar to meropenem). Conclusions: Sulopenem demonstrated excellent in vitro activity versus bacterial pathogens recovered from the urine of Canadian patients. These data suggest that sulopenem may have a role in the treatment of urinary infections caused by antimicrobial-resistant Enterobacterales, but additional clinical studies are required.